Efficient Regeneration of Eucalyptus urophylla x Eucalyptus grandis from Stem Segment - Lejun Ouyang; Zhenchi Huang; Longyan Zhao; Yuee Sha; Fuhua Zeng; Xiangyang Lu (Brazilian Archives of Biology and Technology, 2012)
The aim of the present study was to establish an efficient regeneration system for the hybrid E. urophylla x E. grandis by means of organogenesis. Stem segments from seedlings were used as explants and cultured in a modified Murashige and Skoog medium (MS), supplemented with 13.2 µM N-phenyl-N'-[6-(2-chlorobenzothiazol)-yl] urea (PBU) and 0.285 µM indole-3-acetic acid (IAA). PBU was a useful growth regulator. After cultivating for 5 d, 96% explants formed callus. After 30 d, the calli obtained were transferred to MS medium containing different combinations of 6-benzyladenine (BA) and naphthalene acetic acid (NAA). Compared with other growth regulator combinations, PBU stimulated more vigorous calli and restrained browning. In addition, a large percentage (91.3%) of the calli induced by PBU showed adventitious buds formation. Shoot elongation was then stimulated on half-strength MS mineral salts medium supplemented with 6.6 µM PBU and 0.285 µM IAA for 20 d. For rooting, the elongated shoots were cultivated on root induction medium containing 2.46 µM indole-3-butyric acid (IBA). Plantlets were then successfully transplanted to a greenhouse. This procedure represented an efficient way of E. urophylla x E. grandis plant regeneration.